Sex differences in time to primary percutaneous coronary intervention and outcomes in patients presenting with ST‐segment elevation myocardial infarction. Issue 4 (16th August 2022) - Savage, Michael L.; Hay, Karen; Murdoch, Dale J.; Walters, Darren L.; Denman, Russell; Ranasinghe, Isuru; Raffel, Christopher
Abstract: Objectives: We assessed sex differences in treatment and outcomes in ST‐segment elevation myocardial infarction (STEMI) patients treated with primary percutaneous coronary intervention (PCI). Background: Historically, delays to timely reperfusion and poorer outcomes have been described in women who suffer STEMI. However, whether these sex discrepancies still exist with contemporary STEMI treatment remains to be evaluated. Methods: Consecutive STEMI patients treated with primary PCI patients over a 10‐year period (January 1, 2010 to December 31, 2019) from a tertiary referral center were assessed. Comparisons were performed between patient's sex. Primary outcomes were 30‐day and 1‐year mortality. Secondary outcomes were STEMI performance measures. Results: Most patients ( n = 950; 76%) were male. Females were on average older (66.8 vs. 61.4 years males; p < 0.001). Prehospital treatment delays did not differ between sexes (54 min [IQR: 44–65] females vs. 52 min [IQR: 43–62] males; p = 0.061). STEMI performance measures (door‐to‐balloon, first medical contact‐to‐balloon [FMCTB]) differed significantly with longer median durations in females and fewer females achieving FMCTB < 90 min (28% females vs. 39% males; p < 0.001). Women also experienced greater rates of initial radial arterial access failure (11.3% vs. 3.1%; p < 0.001). However, there were no significant sex differences in crude or adjusted mortality between sexes at 30‐days (3.6% male vs. 5.1% female; p = 0.241, adjusted OR: 1.1, 95% CI: 0.5–2.2, p = 0.82) or at 1‐year (4.8% male vs. 6.8% female; p = 0.190, adjusted OR: 1.0, (95% CI: 0.5–1.8; p = 0.96). Conclusion: Small discrepancies between sexes in measures of timely reperfusion for STEMI still exist. No significant sex differences were observed in either 30‐day or 1‐year mortality.